The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0100-67622010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Caesalpinia leiostachya (benth.) ducke seeds classified by size and shape

Abstract: 4RESUMO -Caesalpinia leiostachya (Benth.) Ducke (pau-ferro) é uma leguminosa arbórea nativa do Brasil, cujas sementes são de diferentes tamanhos e formas, apresentando dormência imposta pela impermeabilidade do tegumento à água. Objetivando melhorar a qualidade do lote, as sementes foram classificadas pela largura em peneiras de crivos circulares (números 13, 14, 15, 16 e 17) e a seguir separadas manualmente pela forma em alongadas, arredondadas e angulares. Foi determinada a massa de 1.000 sementes, medida a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Studies with larger seed species showed positive results in overcoming coat dormancy with the use of sulfuric acid, as in Leucena diversifolia (Souza et al, 2007), Caesalpinia leiostachya (Biruel et al, 2010), and Colubrina glandulosa (Brancalion et al, 2011). These researchers observed that a successful treatment is related to the species and acid exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with larger seed species showed positive results in overcoming coat dormancy with the use of sulfuric acid, as in Leucena diversifolia (Souza et al, 2007), Caesalpinia leiostachya (Biruel et al, 2010), and Colubrina glandulosa (Brancalion et al, 2011). These researchers observed that a successful treatment is related to the species and acid exposure time.…”
Section: Resultsmentioning
confidence: 99%
“…That result may have occurred due to the greater amount of the reserves present in the medium and large-sized seeds. The seeds with greater reserve germinate more uniformly and at a higher percentage and seedling vigor is directly related to seed size, which justifies the adoption of size classes for the production of seedlings (Biruel, Paula, & Aguiar, 2010). Such results are of great relevance, since the production of seedlings in a short period of time is desirable as far as agronomic issues and those related to cost reduction are concerned.…”
Section: Resultsmentioning
confidence: 99%
“…Autores como Malcolm et al (2003), Biruel et al (2010); Alves et al (2005) verificaram que as sementes mais pesadas germinaram de forma mais uniforme e em maior percentual e que o vigor das plântulas encontra-se diretamente relacionado com o tamanho das sementes o que para estes autores justifica a adoção de classes de tamanho para a produção de mudas. Para os tempos de embebição verificou-se que as sementes pequenas a partir de 24 horas de embebição apresentaram um desenvolvimento mais pronunciado do sistema radicular.…”
Section: Resultsunclassified